Triggering tumorigenic signaling: Succinate dehydrogenase inhibitor (SDHi) fungicides induce oncometabolite accumulation and metabolic shift in human colon cells - Carolina Duarte Hospital; Arnaud Tête; Kloé Debizet; Clémence Rives; Jules Imler; Sofiane Safi-Stibler; Lara Gales; Floriant Bellvert; Julien Dairou; Auriane Hagimont; Agnès Burel; Dominique Lagadic-Gossmann; et al. (Environment International)
Succinate dehydrogenase inhibitors (SDHi) are fungicides used worldwide to control the proliferation of fungi in crops. They act by blocking the activity of succinate dehydrogenase (SDH), a universal enzyme involved in mitochondrial functions and metabolism. While SDH-encoding genes are tumour suppressors, which loss-of-function mutations predispose to different types of rare tumors in humans, the consequences of chemical inactivation of SDH by SDHi remain largely unknown, particularly regarding their carcinogenic potential. Here, we investigated the metabolic and cellular impact of SDHi on human non-cancer and transformed colon cells. We show that SDHi inhibit SDH activity and increase the level of succinate, known to act as an oncometabolite in SDH-deficient cancers. SDHi exposure also induces a Warburg-like metabolic reprogramming typical of cancer cells, associated with transcriptomic and morphological changes promoting cell migration and invasion. These effects are enhanced in transformed colon cells carrying mutations in colorectal cancer (CRC) driver genes. These findings provide the first evidence that SDHi-mediated chemical inactivation of SDH mimics some metabolic and phenotypic features previously described in human tumors with SDH genetic deficiencies. Given that loss of SDH expression in CRC patients correlates with a poor prognosis, these patients could represent a population sensitive to SDHi exposure. Therefore, it would be wise to include them in biomonitoring programs. Finally, our work highlights the need to improve regulatory assessment procedures to take better account of SDHi mode of action, by developing relevant tests to cover the multiple key events linked to SDH inactivation and assess the resulting mitochondrial toxicity.